Formulation Of Anti-Acne Extract Aloe Vera (Aloe vera (L.) Burm.f.) In Hibiting The Activity Of Propionibacterium acnes - Mohd. Bilal; Minda Sari Lubis; Rafita Yuniarti; Haris Munandar Nasution (International Journal of Health and Pharmaceutical (IJHP), 2023)
Aloe vera (Aloe vera (L.) Burm.f.) is widely used as an alternative medicine to treat various types of diseases and is now widely used as an antibacterial, one of which is against the acne bacteria Propionibacterium acnes. The purpose of this study was to determine the gel preparation of aloe vera extract (Aloe vera (L.) Burm.f.) which has activity against  Propionibacterium acnes and to see if the gel preparation produced has good and stable quality. Aloe vera ethanol extract was made by maceration method, then the extract was made in a gel preparation and then tested for antibacterial activity against  Propionibacterium acnes by the agar diffusion method using several concentration variations: 2.5%, 5%, and 10%. Furthermore, the inhibitory power of 2.5% has a medium category, the inhibition of 5% has a medium category, and the inhibition of 10% has a strong category. then tested for organoleptic, homogeneity test, pH dispersion and physical stability of the preparation. The results of the study showed that the gel preparation of aloe vera extract had antibacterial activity against Propionibacterium acnes, namely a concentration of 2.5% inhibition zone of 8.8 mm including the medium category, 5% concentration of the inhibitory zone of 9.8 mm including the medium category, the concentration of 10 % with an inhibition zone of 12.9 mm including the strong category. The conclusion of this study is that the gel preparation of 10% aloe vera ethanol extract concentration has the best inhibition. Then the stability test was then carried out, which included, the organoleptic did not change significantly, the homogeneity test showed good results, while the dispersion test showed good results, and the pH test showed good results according to skin pH.